No association of genetic variants in TLR4, TNF-α, IL10, IFN-γ, and IL37 in cytomegalovirus-positive renal allograft recipients with active CMV infection-Subanalysis of the prospective randomised VIPP study. - Pascale Mazzola; Elke Schaeffeler; Oliver Witzke; Martin Nitschke; Volker Kliem; Max Zortel; Eva-Maria Wagner; Matthias Schwab; Ingeborg A Hauser (PLoS ONE)
Background Cytomegalovirus (CMV) infection is amongst the most important factors complicating solid organ transplantation. In a large prospective randomized clinical trial, valganciclovir prophylaxis reduced the occurrence of CMV infection and disease compared with preemptive therapy in CMV-positive renal allograft recipients (VIPP study; NCT00372229). Here, we present a subanalysis of the VIPP study, investigating single nucleotide polymorphisms (SNPs) in immune-response-related genes and their association with active CMV infection, CMV disease, graft loss or death, rejection, infections, and leukopenia. Methods Based on literature research ten SNPs were analyzed for TLR4, three for IFN-γ, six for IL10, nine for IL37, and two for TNF-α. An asymptotic independence test (Cochran-Armitage trend test) was used to examine associations between SNPs and the occurrence of CMV infection or other negative outcomes. Statistical significance was defined as p<0.05 and Bonferroni correction for multiple testing was performed. Results SNPs were analyzed on 116 blood samples. No associations were found between the analyzed SNPs and the occurrence of CMV infection, rejection and leukopenia in all patients. For IL37 rs2723186, an association with CMV disease (p = 0.0499), for IL10 rs1800872, with graft loss or death (p = 0.0207) and for IL10 rs3024496, with infections (p = 0.0258) was observed in all patients, however did not hold true after correction for multiple testing. Conclusion The study did not reveal significant associations between the analyzed SNPs and the occurrence of negative outcomes in CMV-positive renal transplant recipients after correction for multiple testing. The results of this association analysis may be of use in guiding future research efforts.